Kampanye Digital TeaIsGood dalam Membentuk Persepsi Konsumen Produk Teh Botol Sosro - Hafiz Firjatullah; Guruh Ramdani (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The rapid development of digital technology has encouraged companies to utilize social media as a communication medium to shape consumer perceptions of products and brands. This study aims to analyze the influence of the TeaIsGood digital campaign on consumer perception of Teh Botol Sosro products through Instagram-based communication. The research employed a quantitative explanatory approach using an online survey of 100 respondents who had been exposed to the campaign. Data were collected through questionnaires and analyzed using simple linear regression with IBM SPSS version 31. The findings indicate that the TeaIsGood digital campaign has a positive and significant effect on consumer perception of Teh Botol Sosro products. The regression analysis shows that the campaign contributes 85.2% to consumer perception. The findings suggest that message credibility, relevance, clarity, and attractiveness are important elements in shaping positive consumer perceptions through digital communication. This study implies that social media campaigns can function not only as promotional tools but also as strategic media for building brand meaning and consumer perception in the fast moving consumer goods (FMCG) industry.